Radio musicale, prolongements numériques et régimes d’interactivité. Le cas de Nostalgie - Séverine EQUOY HUTIN (Tic & Société)
Web radio asks the listener to set aside the exclusivity of sound and a logic of flow in favor of a logic of storage and direct, non-linear access to information. Interactivity is the main promise of Web 2.0: listening to an audiovisual offer is replaced by a system that decontextualizes content and favours fragmentation, availability and aggregation. This re-mediation involves new forms of writing, new modalities of perception and consumption, as well as a new relation with the media. Radio has lengthy experience with interactivity but the case of musical radio is particular in that its programming grid doesn’t offer much space for “talk” or interaction. Furthermore, musical radio must compete with “new mediators” of music. In this context, we focus on the case of the French radio station Nostalgie, with the hypothesis that its various digital extensions (mobile application and web site) implement new ways to discover and/or enjoy music.